Larvicidal Activity of Citrus aurantifolia Decoction against Aedes aegypti Larvae - Priyanka Devi Muniandy; Silvita Fitri Riswari; Kartika Ruchiatan (Althea Medical Journal, 2020)
Background: Infected female Aedes mosquito is the primary vector of virus transmission for dengue hemorrhagic fever (DHF). Natural phytochemical larvicide is becoming a complementary way for vector control management. The citrus plant extract has natural chemical reactions against mosquito larvae. This study aimed to identify the larvicidal activity of Citrus aurantifolia leaves decoction against larvae of Aedes aegypti as an effort to discover natural phytochemical repellant.Methods: This was an analytic experimental study using twenty-five Aedes aegypti larvae. The larvae were placed in translucent cups containing different concentrations of C. aurantifolia leaves decoction. The cups were filled with Abate as positive controls and water as negative controls. The experiment was repeated for three consecutive days, and the mortality of larvae was monitored for 48 hours as described in the World Health Organization (WHO) guidelines for laboratory and field testing for mosquito larvicides (WHOPES).Results: C.aurantifolia decoction significantly decreased the number of larvae. The highest mortality was shown in 30% concentration with a total of 224 dead larvae. Probit analysis showed LC50 was 38.5% and 6.6% at 24 and 48 hours, respectively. The highest rate of killing the larvae was taken at LC60 with 91.6% for 24 hours and LC65 64.4% for the 48 hours; thus LC90 could not be determined. The significance of the decoction concentration was analyzed by one way ANOVA preceded with Post-hoc test (p-values 0.000).Conclusions: Decoction of C.aurantifolia leaves has proved to have larvicidal activity against larvae of Aedes aegypti and could be used as phytochemical larvicides in controlling vector of DHF.